Problems of teaching students with special needs - Kamaeva, Rima; Kvasnikova, Tatiana; Egorova, Maria; Kashapova, Lyalya (Opción, 2019)
The purpose of this study is to identify the main problems in obtaining quality higher education for students with special needs, and also to find out whether graduates with special needs can compete in the labor market. The survey was conducted using an online survey among two groups of respondents. The results of the study indicate that more than half of universities (65 percent) have ramps, elevators, and lifting devices. In conclusion, the administration of all universities must ensure that all students in this group will be provided with the necessary training materials, equipment, and appropriate teaching staff